Relationship between the optical gap and the optical-absorption tail breadth in amorphous GaAs - da Silva, JHD; Campomanes, R. R.; Leite, DMG; Orapunt, F.; O'Leary, S. K. (American Institute of Physics (AIP), 2004)
We study the relationship between the optical gap and the optical-absorption tail breadth for the case of amorphous gallium arsenide (a-GaAs). In particular, we analyze the optical-absorption spectra corresponding to some recently prepared a-GaAs samples. The optical gap and the optical-absorption tail breadth corresponding to each sample is determined. Plotting the optical gap as a function of the corresponding optical-absorption tail breadth, we note that a trend, similar to that found for the cases of the hydrogenated amorphous silicon and hydrogenated amorphous germanium, is also found for the case of a-GaAs. The impact of alloying on the optical-absorption spectrum associated with a-GaAs is also briefly examined. (C) 2004 American Institute of Physics.